ChemInform Abstract: Zr‐Based Metal—Organic Frameworks: Design, Synthesis, Structure, and Applications. Issue 22 (12th May 2016) - Bai, Yan; Dou, Yibo; Xie, Lin‐Hua; Rutledge, William; Li, Jian‐Rong; Zhou, Hong‐Cai
Abstract: Review: 300 refs.